2019
DOI: 10.1021/acsnano.9b01581
|View full text |Cite
|
Sign up to set email alerts
|

Substrate Metabolism-Driven Assembly of High-Quality CdSxSe1–x Quantum Dots in Escherichia coli: Molecular Mechanisms and Bioimaging Application

Abstract: Biosynthesis offers opportunities for cost-effective and sustainable production of semiconductor quantum dots (QDs), but is currently restricted by poor controllability on the synthesis process, resulting from limited knowledge on the assembly mechanisms and the lack of effective control strategies. In this work, we provide molecular-level insights into the formation mechanism of biogenic QDs (Bio-QDs) and its connection with the cellular substrate metabolism in Escherichia coli. Strengthening the substrate me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 57 publications
5
52
0
Order By: Relevance
“…3a ). Among various biomineralized nanoparticles (such as FeS, CdSe, Ag and Pd nanoparticles) 20 , 32 34 , FeS nanoparticles were selected for SP collector assembly due to their ease of biosynthesis, high electroactivity and biocompatibility 35 37 . To confine the nanoparticles in the periplasm and on the outer membrane surface, a diffusion-confined biosynthesis strategy was developed (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3a ). Among various biomineralized nanoparticles (such as FeS, CdSe, Ag and Pd nanoparticles) 20 , 32 34 , FeS nanoparticles were selected for SP collector assembly due to their ease of biosynthesis, high electroactivity and biocompatibility 35 37 . To confine the nanoparticles in the periplasm and on the outer membrane surface, a diffusion-confined biosynthesis strategy was developed (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that substrate metabolism regulation greatly affected the fluorescence property of the nanoparticles synthesized by Escherichia coli [6b] . Thus, it is speculated that the crystalline structure of CdS QDs may be controlled by regulating the substrate metabolism of microorganism.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, it was hypothesized that glutathione content plays an essential role in the intracellular growth of the NPs [117]. Recently, Tian et al relied on glucose to increase the synthesis rate of CdS x Se 1−x QDs of ~2 nm in size using E. coli JM109 [132]. This effect was attributed to an enhanced synthesis of NADPH and reduced thiol (-SH) groups that directly improved the tolerance to metal toxicity and NP mineralization.…”
Section: Using Bacteriamentioning
confidence: 99%
“…Besides, the cell viability was monitored every 20 min for 6 h. Neither imaging process nor QDs caused adverse or toxic effects [201]. Lastly, the in vivo bioimaging of MDA-MB-231 breast cancer cell line in mice was performed using fluorescent CdS x Se 1−x QDs synthesized using E. coli [132].…”
Section: Bioimaging Biodetection and Biosensingmentioning
confidence: 99%